The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.15809/irriga.2011v16n3p301
|View full text |Cite
|
Sign up to set email alerts
|

Determinação Do Padrão Do Manejo Da Irrigação Praticada No Perímetro Irrigado Baixo Acaraú, Ceará, via Análise Multivariada

Abstract: RESUMOO objetivo do presente trabalho foi avaliar o padrão da irrigação no Perímetro Irrigado Baixo Acaraú no Estado do Ceará, através da aplicação de questionários e da avaliação do desempenho dos sistemas de irrigação bem como fazer uma análise integrada da similaridade dos irrigantes através da análise de agrupamento. A análise de campo foi realizada em duas etapas: a primeira em setembro de 2006, com a aplicação de questionário a 18 irrigantes; e a segunda em julho de 2007, quando foram efetuadas as avalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…According to Lopes et al (2011), when conducting interviews with lot owners in the Lower AcaraúIrrigation Perimeter, they found that 77.78% of the producers had had no experience with irrigated agriculture before arriving in the area. They concluded that existing irrigation management in the perimeter was inadequate, and that producers could not determine when or how much to irrigate.…”
Section: Producer Profilementioning
confidence: 99%
See 1 more Smart Citation
“…According to Lopes et al (2011), when conducting interviews with lot owners in the Lower AcaraúIrrigation Perimeter, they found that 77.78% of the producers had had no experience with irrigated agriculture before arriving in the area. They concluded that existing irrigation management in the perimeter was inadequate, and that producers could not determine when or how much to irrigate.…”
Section: Producer Profilementioning
confidence: 99%
“…The activity emerged in the Northeast of Brazil following a significant growth in the market, and has resulted in greater production and higher incomes for the sector, especially fruit farming, which has assumed a prominent place in this scenario (Lopes et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is highly susceptible to pests and diseases, and has high demand for inputs and services, which lead to high financial investment per unit area. Furthermore, Lopes and others [4] remarked that good productivity requires availability of water throughout the cycle [5], as the tomato plant is very sensitive to water stress. The commercial value of the table tomato is defined by the characteristics and quality of the fruit [6].…”
Section: Introductionmentioning
confidence: 99%
“…Get values from the crop water consumption through evapotranspiration estimates is essential for sizing and management of irrigation systems, mainly because it is growing awareness of the importance of water resources (Lopes et al, 2011;Rodrigues et al, 2011).…”
Section: Introductionmentioning
confidence: 99%